The influence of Brachylaena huillensis O. hoffm on diversity, abundance and structure of Mtunguru Forest Reserve in Tanzania - Dickson Gerald Mauki; Orestus Kinyero; Filbert Meela (Environmental and Sustainability Indicators, 2023)
This paper reports current ecological status of B. huillensis in Mtunguru Forest Reserve (MFR) using 90 sample plots of 400 m2 at 500 m intervals along 10 transects. The forest composition was assessed in terms of stem density, basal area and diameter class distribution of tree species including species of B. huillensis. The results revealed that the status of the forest was declining due to illegal harvesting of forest products such as firewood, construction materials and charcoal burning. It was observed that B. huillensis occurred in all 90 sample plots out of 94 tree species recorded, the B. huillensis contributed 38% of total tree density and frequency of hundred percent. Total density of trees ≥5 cm DBH was 380 tree stems ha−1 with a Basal area of 12 m2 ha−1, where the share of B. huillensis stems was 143 ha-1 with a basal area of 6.01 m2 ha−1. The stem size class distribution of species showed less density of individuals in lowest girth class (5–10 cm DBH) and the same for B. huillensis was observed in girth class (< 16 cm DBH). The result indicates the recruitment young individuals are severely affected probably because of high disturbance of the forest understory. This study indicates poor conservation status of forest reserve under Miombo woodland and status of B. huillensis under threatened category, and thus better forest management plans are needed to ensure sustainable livelihood of the inhabitants.